Analysis of a genotype G3P[9] rotavirus a strain that shows evidence of multiple reassortment events between animal and human rotaviruses. Issue 6 (5th December 2016) - Bezerra, Delana A.M.; Guerra, Sylvia F.S.; Serra, Ana C.S.; Fecury, Priscylla C.M.S.; Bandeira, Renato S.; Penha, Edvaldo T.; Lobo, Patrícia S.; Sousa, Edivaldo C.; Linhares, Alexandre C.; Soares, Luana S.; Mascarenhas, Joana D.P.
Abstract : The species A rotaviruses (RVA) are important gastroenteric pathogens that infect humans and animals. RVA genotype G3P[9] has been described in human‐animal reassortment events, and the complexity of its hosts motivates the genetic investigation of this strain. Therefore, the aim of this study is to analyse a G3P[9] sample that was detected in a child with acute gastroenteritis. The 1A3739 sample featured the constellation G3P[9]‐I18‐R3‐C3‐Mx‐A19‐N3‐T3‐E3‐H6. The sequence for VP3 gene was not obtained. The phylogeny showed a closer relationship among genes VP7, VP1, NSP3, NSP4, and NSP5 with genes of animal origin, such as chiropter, alpaca, equine, and simian. In addition, the genes VP6 and NSP1 belong to the new genotypes I18 and A19, respectively. The emergence of strains such as these can interfere with the effectiveness of the RVA vaccine, and continuous monitoring is therefore important. Additional studies are needed to determine the evolutionary source and to identify a possible reservoir of RVA in nature.